2019
DOI: 10.1186/s12876-019-1004-2
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D levels are associated with high viral loads in patients with chronic hepatitis B: a systematic review and meta-analysis

Abstract: Background Previous studies have investigated the vitamin D status in patients with chronic hepatitis B virus (HBV) infection and its relationship with HBV replication, the results however were inconsistent. The present meta-analysis was carried out to compare the vitamin D levels between patients with chronic hepatitis B (CHB) and healthy controls, and to determine whether vitamin D levels were correlated with HBV viral loads significantly. Methods A systematic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…Table 4 presents findings from various studies. CHB 25(OH)D concentrations were lower in CHB patients than that of healthy controls and inversely correlated with HBV viral loads [110] KSHV Found that cathelicidin significantly reduced KSVH by disrupting the viral envelope. [111] HIV-1 Review of 29 clinical studies of vitamin D supplementation showed there was a decrease in inflammation.…”
Section: Clinical and Epidemiological Findings Regarding Covid-19mentioning
confidence: 97%
“…Table 4 presents findings from various studies. CHB 25(OH)D concentrations were lower in CHB patients than that of healthy controls and inversely correlated with HBV viral loads [110] KSHV Found that cathelicidin significantly reduced KSVH by disrupting the viral envelope. [111] HIV-1 Review of 29 clinical studies of vitamin D supplementation showed there was a decrease in inflammation.…”
Section: Clinical and Epidemiological Findings Regarding Covid-19mentioning
confidence: 97%
“…[109] CHB 25(OH)D concentrations were lower in CHB patients than that of healthy controls and inversely correlated with HBV viral loads [110] KSHV Found that cathelicidin significantly reduced KSVH by disrupting the viral envelope. [111] HIV-1…”
Section: Virus Vitamin D Effect Referencementioning
confidence: 99%
“…The influence of VD on chronic liver diseases has been thoroughly described in various studies regardless of etiologies. Serum VD levels were inversely correlated with HBV VL in patients with chronic hepatitis B [ 26 , 27 ]. Low serum 25(OH)VD levels were associated with advanced disease and were also a predictor of response with ursodeoxycholic acid in primary biliary cholangitis patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%